The other F word [videorecording (DVD)] - Blaugrund, Andrea; Alexakis, Art; Lindberg, Jim; Hawk, Tony; Flea (Musician) (Oscilloscope Laboratories, 2012)
Revealing, hilarious, and touching, The Other F Word asks what happens when a generation's ultimate anti-authoritarians - punk rockers - become society's ultimate authorities - fathers. With a large chorus of punk's leading men, this film follows Jim Lindberg through his hysterical and moving journey from belting his band's anthem to embracing his newfound role in mid-life: fatherhood.